Influence of screw head diameter on ex vivo fixation of equine lateral condylar fractures with 5.5 mm cortical screws. Issue 4 (18th March 2022) - Constant, Caroline; Zderic, Ivan; Arens, Daniel; Pugliese, Brenna; Gehweiler, Dominic; Gueorguiev‐Rüegg, Boyko; Zeiter, Stephan
Abstract: Objective: To determine the influence of screw head diameter on equine condylar fracture fixation with 5.5 mm cortical screws. Study design: Ex vivo, biomechanical study, blinded, matched‐pair design. Sample population: Fifteen pairs of equine third metacarpal (MC3) bones. Methods: Lateral condylar fractures were simulated by parasagittal osteotomies and repaired pairwise by 2 × 5.5 mm cortical screws of 8 mm (standard) or 10 mm (modified) head diameter. Interfragmentary compression at maximum screw insertion torque was measured. The instrumented specimens were pairwise stratified for biomechanical testing under the following modalities (n = 5): (1) screw insertion torque to failure, (2) quasi‐static axial load to failure, and (3) cyclic axial load to 2 mm displacement followed by failure. Tests (1) and (2) were analyzed for yield, maximum, and failure torque/angle and load/displacement, respectively. Number of cycles to 2 mm displacement and failure was assessed from test (3). Results: Maximum insertion torque was greater, and failure angle smaller, when constructs repaired with modified screws were tested (8.1 ± 0.5 vs. 7.4 ± 0.5 Nm; P = .0047 and 550 ± 104 vs. 1130 ± 230; P = .008). Axial yield (7118 ± 707 vs. 5740 ± 2267 N; P = .043) and failure load (12 347 ± 3359 vs. 8695 ± 2277 N; P = .043) were greater for specimens repaired with modified screws. No difference was detected between constructs in the number of cycles to 2 mm displacement. Conclusion: Condylar MC3 osteotomies repaired with modified 5.5 mm cortical screws sustained greater maximal hand torque insertion, smaller insertion failure angle and 1.4 fold greater quasi‐static failure forces than constructs repaired with standard 5.5 mm screws. Clinical significance: Use of modified screws with larger heads may improve the fixation of condylar fractures in horses. These results provide evidence to justify clinical evaluation in horses undergoing fracture repair.